(untitled) (Journal of Comparative & International Higher Education, 2023)
Today’s increasingly heterogeneous world imposes demands on higher education institutions to develop university students’ intercultural competence (IC) so that they respond constructively to the cultural challenges of the 21st century. This study aims to explore the impact of short-term study abroad programs on the development of students’ intercultural competence. 17 semi-structured interviews were conducted with Myanmar undergraduates who participated in study-abroad programs to get an in-depth understanding of their study abroad experiences. Thematic analysis was employed to examine how these programs influence their attitudes toward the native culture, the host culture and cultural differences, and their intercultural interaction. The main findings reveal that study abroad enhances students’ IC, confirming the five elements of IC by Deardorff (2008): attitudes, knowledge and comprehension, skills, desired internal outcomes, and desired external outcomes, with an emerging aspect ‘recommendation’ based on ‘cultural reflection’. Specific implications are offered to university administrators and decision-makers of Myanmar higher education on the basis of the findings.